Photocatalytic Reduction of CO2 with Water into Methanol and Ethanol Using Graphene Derivative-TiO2 Composites: Effect of pH and Copper(I) Oxide - L. M. Pastrana-Martínez (2016)
Fuels derived from CO2 can contribute to neutralize the carbon balance in the atmosphere and can be converted into easily transportable liquid chemicals, such as methanol (MeOH) or ethanol (EtOH). In this work, a composite prepared from graphene oxide (GO) and titanium dioxide (TiO2) is applied to the photocatalytic water reduction of CO2 into renewable fuels under UV/vis light irradiation. The pH was identified as a key variable towards selective MeOH formation. The prepared GO-TiO2 composite exhibited superior photocatalytic activity for EtOH production (144.7 mu mol g(-1) h(-1)) at pH 11.0 and for MeOH production (47.0 mu mol g(-1) h(-1)) at pH 4.0. The effect of copper species in the GO-TiO2 composite is also assessed and its influence on the photocatalytic reaction inferred. The photocatalysts prepared with copper nitrate as copper precursor exhibited the highest rate of MeOH production at pH 11.0. Accordingly, a conceptual scheme in which the photogenerated electrons are used to reduce CO2 is proposed.